The Role of MathXL in the Online Learning of Algebra - Zogheib, Bashar (2012)
The purpose of this study is to explore and describe the impact that platforms such as MathXL can have on students’ attitudes and performance in college algebra classes. MathXL is an innovative series of text-specific online courses that is available for Pearson textbooks in mathematics and statistics. Two groups of students are considered in this paper. The first group is assigned homework through MathXL while the second group is assigned homework through the traditional in-class instruction. Although no statistically significant differences are found between the groups’ final scores, inferential statistics, as well as the qualitative findings, reveal that students who are taught using MathXL outperformed those who are not. Moreover, positive attitudes towards MathXL are dominant.